Penambahan Tepung Daun Katuk (Saurupus Androgynus L. Merr) dalam Ransum Terhadap Pertambahan Berat Badan dan Lingkar Scrotum Kambing Jantan Peranakan Ettawa - Dedhi Yustendi; Dasrul Dasrul; Didy Rachmadi (Agricultural Faculty, 2013)
The addition of katuk leaf meal (saurupus androgynus l.merr) in feeds on body weight gain and scrotal circumference male ettawa grade goatsABSTRACT. This research was aimed to study the effect of addition of katuk leaf meal (Sauropus androgynus L. Merr) in feed on body weight gain and scrotal circumference of male Ettawa grade goat. The research lasted for eight months, starting Agustus 2012 to Maret 2013, with feeding trial for two months. Twenty male Ettawa grade goats of 18 to 24 months old, were divided into 4 treatment groups. Treatment groups were added with 0% Katuk leaf meal (R0); 5% (R1); 10% (R2) and 15% (R3), with 5 goats in each replication. Treatment diets were feed in the morning and afternoon for 60 days. Weighing body weight and measuring scrotal circumference was done every week. Data were analyzed using analysis of variance (ANOVA) and if there was significantly different, the data were further tested using Duncan multiple range test. The result shows that the body weight gain of the treatment were, R0 (2,39 0,43 kg); R1 (2,84 0,36 kg); R2 (2,85 0,20 kg) and R3 (3,42 0,78 kg) respectively. Scrotal circumference were, R0 (0,74 0,10 cm); R1 (1,24 0,26 cm); R2 (1,26 0,40 cm) dan R3 (1,32 0,32 cm) respectively. The result of this research indicated that the addition of katuk leaf meal in feed had significant effects (P0,05) on body weight gain and scrotal circumference of Ettawa grade goat.